Inclusion of levels of cotton expeller in the feeding of confined sheep: productive behavior, carcass characteristics and meat quality - Jorge Daniel Caballero Mascheroni; Guido Arnaldo Portillo; Javier Feliciano González Cabañas; Luis Alberto Alonzo Griffith; Tania Fariña Díaz; Nicolas Daniel Prieto Quevedo (Manglar)
To substitute soybean meal with different levels of cottonseed meal, twelve non-castrated male Santa Inés × Dorper sheep with an average initial weight of 27.33 ± 0.58 kg and age of 225 ± 15 days were used. The treatments consisted of three levels of cottonseed meal (0%, 15%, and 30%), with four replicates, distributed in a completely randomized experimental design. The diets consisted of totally mixed rations, with a forage-concentrate ratio of 30:70 (dry matter basis). Cottonseed meal levels did not affect (p > 0.05) dry matter intake for up to 28 days, then values decreased linearly. Feed conversion and daily weight gain were improved up to 28 days and then decreased linearly (p ≤ 0.05)In the same way, cooling and cooking weights losses and the shear force were affected and with a quadratic behavior (p ≤ 0.05) by the levels of cottonseed meal, standing out the level of 15%, while the live weight, hot and cold carcass weight and yield, loin eye area, the thickness of subcutaneous fat were not affected by the treatments (p > 0.05). Cottonseed meal can replace up to 20% of the soybean meal in sheep concentrate feed for a period not to exceed 28 days.